A LITERARY STUDY ON THE NATURE OF QUESTION AND ITS TECHNIQUES IN LEARNING - Guspatni Guspatni (Ta'dib, 2017)
Questioning is a form of communication that supports learning. Questions asked during learning process can be used to evaluate students’ understanding on certain concepts. Through questioning, an educator can direct students to think and get involved in learning activities. However, asking good questions for cognitive functions is difficult. Low response from students discourages the educator to either ask or give more questions during the teaching and learning process. In this writing, types of questions, functions of questions, aims of questions, and questioning techniques are discussed. This article further provides sample questions in learning science.